(untitled) - Kwitz, Mary DeBall; Degen, Bruce (New York, N.Y., 1983)
Little Chick becomes hungrier and hungrier and more and more impatient as she watches all the other barnyard animals getting their breakfast before she gets hers.
Keywords: Juvenile fiction; Chickens; Juvenile fiction; Domestic animals; Early Readers